Woman and Authority in Ian McEwan’s “Conversation with a Cupboard Man” and Its Film Adaptation - Sumera, Adam (Text Matters: A Journal of Literature, Theory and Culture, 2011)
The paper analyzes Ian McEwan's short story "Conversation with a Cupboard Man" (published in 1975) and its film adaptation made in Poland by director Mariusz Grzegorzek in 1993. In many works McEwan shows women in more positive light than men. This short story, however, deals with a mother's total domination of her son's life. The text is in the form of first-person narration of the son but it is the figure of the mother that is of utmost importance. The protagonist describes his life from his childhood. His mother wanted him to remain a baby as long as possible, depriving him of free will and leaving him totally dependent on her. Her attitude changed when she found a partner. The protagonist, now seventeen, had rapidly to grow up from a baby into an adult. Childhood and total passivity remain for him ideals to be pursued, and a cramped cupboard becomes his favourite environment. The influence of his upbringing remains with him for ever. After analyzing the short story the paper explores parallels to other works by McEwan and other writers. The importance of the use of the indeterminate article in the title is discussed. Attention is given to the issue of defamiliarization. And the ambivalent attitude of the protagonist towards his mother is examined. The second part of the paper deals with the film adaptation. Grzegorzek has imaginatively developed the short story into a full-blown feature film. It preserves most of the important elements of the short story, at the same time providing new material largely in keeping with the original's tone. The director not only extrapolates, inventing new scenes to fill in the short story's unspoken gaps but also skilfully changes the narrator's comments into scenes, and this is not purely a change from telling into showing. The paper discusses the imagery of the movie, especially Oedipal motifs, references to Christ, and the impression of blood-red lips. It stresses the stronger role of the teacher from the home (Smith in the text) and his influence on the only independent action of the protagonist—the revenge on Pus-face. It is also important that the film omits any verbal expression of the protagonist's hatred towards his mother.